THE ENERGY INDUSTRY IN THE KYRGYZ REPUBLIC: URRENT STATE,PROBLEMS, AND REFORMS - BAUM, Ludmilla (CENTRAL ASIA AND THE CAUCASUS, 2008)
The energy industry is of special importance to Kyrgyzstan. Most of the electric power generated is used to meet the economy’s intermediate needs in industrial and agricultural production. At present, Kyrgyzstan’s energy sector, which has a large share of the republic’s GDP, is threatened with a significant drop in its potential due to: —the imbalanced use of hydropower resources necessary for generating electricity caused by the low-water level period; —the high level of physical and moral wear and tear of the operating equipment due to the long absence of investments; —unstable financial and economic activity, as well as the increase in technical and commercial losses. This sector can consequently become a potential source of macroeconomic instability for the country, thus undermining the efforts being made to achieve stable economic growth. The current restructuring of the energy industry has liberalized the electricity sector to a certain extent, which has helped to make spending on the production, transmission, and distribution of electricity, as well as the formation of tariffs for thermal and electric power, more transparent. But this has not led to the anticipated improvement in the economic indices of the energy system. There is still a long way to go. In this respect, an acute need has arisen to improve management of the sector in order to increase the efficiency and economic benefits and develop new approaches in energy policy. In turn, this is giving rise to the need to reach a higher level of reform in the sector, which should also include a system of measures for creating conditions aimed at developing the energy market. What reforms in particular does Kyrgyzstan need? There are quite a few different opinions on this issue. Reforms are a complicated issue since any mistakes could lead not only to a production slump in the country, but also to a shortage of fuel and energy resources, stagnation of the agrarian sector, an imbalance in the fiscal system, and the emergence of investment problems that will leave the republic dependent on foreign partners. Whereby issues relating to the development of Kyrgyzstan’s electric power industry are directly related to the problems neighboring countries are facing in enhancing their energy industries. All of this naturally focuses attention on political, economic, technical, and other aspects of energy industry reform. The Kyrgyz Republic’s energy policy is aimed at ensuring energy independence, more reliable and steady operation of the energy system, balanced electric power production and consumption, and an increase in export potential.